Building manageable web services from the ground up the management criteria developers must consider. - Foody, Dan (XML journal :the ultimate enterprise resource.)
Life is full of compromises and application development is no exception to the rule. So, when that project deadline is looming (and it always is) you are faced with three options: 1. Finish the functional application, 2. Ensure that the application is manageable. 3. Ask your manager for more time so you can accomplish both